Esophageal Lichen Planus: Understanding a Potentially Severe Stricturing Disease - Bharat Rao; Abhishek Gulati; Blair Jobe; Shyam Thakkar (Case Reports in Gastrointestinal Medicine)
A 67-year-old woman with a long-standing history of recurrent dysphagia and esophageal strictures failed to respond to aggressive antireflux management. She required multiple dilations for symptomatic strictures that were discovered throughout the esophagus. Intralesional, topical, and systemic glucocorticoid therapies were utilized without resolution in symptoms. Several years after initial presentation, histopathology ultimately demonstrated lichenoid features and a diagnosis of esophageal lichen planus (ELP) was confirmed. However, as her symptoms had already become significantly disabling with severe strictures that carried an increased risk of endoscopic complications with dilation, she ultimately decided to undergo an esophagectomy for definitive treatment. Moreover, ELP may often go unrecognized for several years. Clinicians should consider ELP in the differential for dysphagia in middle- to elderly-aged women with or without a known history of lichen planus (LP) especially for those with findings of multiple or proximal strictures.